2010
DOI: 10.2174/1876523801003010001
|View full text |Cite
|
Sign up to set email alerts
|

Partial Dopamine D2/Serotonin 5-HT1A Receptor Agonists as New Therapeutic Agents~!2009-12-17~!2010-04-07~!2010-07-20~!

Abstract: Abstract:The therapeutic efficacy of current antipsychotic or antidepressant agents still present important drawbacks such as delayed onset of action and a high percentage of non-responders. Despite significant advancements in the development of new drugs with more acceptable side-effect profiles, patients with schizophrenia or major depression experience substantial disability and burden of disease. The present review discusses the usefulness of partial dopamine D 2 /serotonin 5-HT 1A receptors agonists in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 163 publications
0
5
0
Order By: Relevance
“…It has been confirmed that disturbed dopaminergic neurotransmission in the mesolimbic and nigrostriatal regions also contributes significantly to the development of depression [ 32 ]. Consequently, intensive research is under way on a new class of potential drugs which exert their effects through interaction with D 2 /5-HT 1A [ 33 ]; where the ligand would be a partial agonist of the 5-HT 1A receptor and would induce postsynaptic serotonergic neurotransmission, which would increase dopamine levels in the mPFC (medial prefrontal cortex) [ 34 ]. The role of 5-HT 2A receptors in the treatment of schizophrenia has also been well documented in numerous publications.…”
Section: Resultsmentioning
confidence: 99%
“…It has been confirmed that disturbed dopaminergic neurotransmission in the mesolimbic and nigrostriatal regions also contributes significantly to the development of depression [ 32 ]. Consequently, intensive research is under way on a new class of potential drugs which exert their effects through interaction with D 2 /5-HT 1A [ 33 ]; where the ligand would be a partial agonist of the 5-HT 1A receptor and would induce postsynaptic serotonergic neurotransmission, which would increase dopamine levels in the mPFC (medial prefrontal cortex) [ 34 ]. The role of 5-HT 2A receptors in the treatment of schizophrenia has also been well documented in numerous publications.…”
Section: Resultsmentioning
confidence: 99%
“…For example, stress, in animal models of depression, activates VTA DA neurons and their limbic efferent targets [ 115 ]. Moreover, the DA system is now one of the targets of depression treatment, for example drugs initially used in schizophrenia like aripiprazole or quetiapine are now used in depressed patients [ 8 ].…”
Section: Effect Of 5-ht 3 Receptor Ligands On Neurmentioning
confidence: 99%
“…Preclinical studies have suggested that targeting specific 5-HT receptors with selective agonist or antagonist drugs may enhance the antidepressant response and reduced its delay compared to currently used antidepressants. Both the 5-HT 1A receptor antagonist pindolol and 5-HT 1A receptor agonists, e.g., buspirone, have been largely investigated both in clinical and in preclinical studies in combination with antidepressants with some significant effects [ 7 , 8 ]. Moreover, the beneficial effect of atypical antipsychotics, such as quietapine, in combination with antidepressants in depression may be partly due to their 5-HT 2A receptor targeting [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The compounds were obtained in a search for a new generation of antipsychotics following the principles of the multitarget strategy. The derivatives were designed for 5-HT 2A and D 2 receptors (the basic profile of pharmaceutical activity of atypical antipsychotics) and, additionally, for 5-HT 1A receptors [19][20][21][22][23][24][25]. With the aim of enhancing cognitive factors and memory, which might be improved by potential antipsychotics [26], the activity of the compounds was expanded to their affinity to 5-HT 1A receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The role played by the 5-HT 1A receptor in the pathomechanism of schizophrenia was related to its regulatory influence on the functions of the prefrontal cortex (PFC), including emotional control, cognitive behavior and working memory [26][27][28][29][30][31]. The goal of the research was to obtain a new generation of antipsychotics which would display a multireceptor mechanism of action, be devoid of many undesired effects such as extrapyramidal symptoms (EPS), tardive dyskinesia or weight gain in patients and many other effects caused by drugs currently used in the pharmacotherapy of schizophrenia [21,22,32].…”
Section: Introductionmentioning
confidence: 99%